A comprehensive investigation of an LTE-enabled smart door system using the Arduino UNO - Hashim Qasim, Nameer; Rahim, Fakher; Bodnar, Nataliia (Edelweiss Applied Science and Technology, 2024)
Traditional residential security systems frequently lack remote access and real-time reaction capabilities, necessitating home automation security technology developments. With the rise of the Internet of Things (IoT), solutions such as the Smart Door are prepared to transcend these constraints by leveraging modern communication technology. The article aims to develop, implement, and evaluate an LTE-enabled Smart Door system built on the Arduino Uno platform. The goal is to improve home security by offering keyless entry, real-time surveillance, and remote operation, increasing user convenience and system reliability. We created a Smart Door system with an Arduino Uno microcontroller and LTE connectivity. The system's performance was measured using a variety of measures, including response time, reliability, and security against unwanted access. Testing included simulation environments and real-world scenarios to ensure the system's operational efficacy and security. The Smart Door system performed admirably, with a reaction time of less than two seconds in 95% of commands and strong resilience to brute force attacks. It effectively incorporated keyless entry, live video streaming, and real-time alarms, all controlled by a smartphone app, demonstrating the system's dependability and efficiency in live scenarios. The LTE-enabled Smart Door system considerably improves over traditional home security options. It provides enhanced security, simple operation, and more outstanding remote management capabilities by utilizing IoT technology. These enhancements fill essential holes in existing systems, providing a safer, dependable, and convenient answer for modern home security requirements.